Comparative analysis of EU and candidate countries resource efficiency - ÇİLİNGİRTÜRK, AHMET METE (My University, 2011)
European Union is a regional integration project with its social and economic objectives. it is an important economic power competing with U.S. at west and with Chine at east. It aims the economic homogeneity of the member states and candidate countries in its region. This study aims to rank 27 EU members and 3 candidate countries according to their assumed input-output structures for the years 2002 and 2006. CCR and BCC Data Envelopment Analysis models were used to determine relative efficiency, so effective and non-effective countries were discriminated. Furthermore Super-Efficiency model of DEA was used to evaluate the effective countries. The findings are interpreted as that the EU achieves some of the specified important objectives.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Çalışma Ekonomisi; Social Sciences and Humanities; Labor Economics and Industrial Relations; Labor Economics; İŞ FİNANSI; Ekonomi ve İş; Sosyal Bilimler (SOC); BUSINESS, FINANCE; ECONOMICS & BUSINESS; Social Sciences (SOC); Finans; Muhasebe; İşletme, Yönetim ve Muhasebe (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Finance; Accounting; Business, Management and Accounting (miscellaneous); Social Sciences & Humanities; Efficiency; Resource Utilization; EU; DEA; Super Efficiency